2011
DOI: 10.1590/s0100-83582011000300015
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade e eficácia de herbicidas inibidores da enzima accase na cultura da mamona

Abstract: O experimento foi conduzido com o objetivo de avaliar a seletividade e eficácia de herbicidas inibidores de ACCase na cultura da mamoneira AL Guarany 2002, no município de Paraguaçu Paulista/SP, durante a safra 2002/2003. O delineamento experimental utilizado foi o de blocos ao acaso, com 11 tratamentos e quatro repetições, constituídos pelos herbicidas e adjuvantes: fluazifop-p-butil (313 g ha-1) + Agral® (0,2% v/v); sethoxydim (322 g ha-1) + Assist®(0,5% v/v); haloxyfop-methyl (120 g ha-1) + Assist® (0,5% v/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
3
0
4
Order By: Relevance
“…* significant by F test (p≤0.05); ns = non significant. Maciel et al (2011) observed lower chlorophyll content in leaves from the AL Guarany 2002 cultivar, according to the application of isoxaflutole in post-emergence, supporting the intoxication observed between day 7 and 28 DAA. Therefore, results obtained with this carotenoid synthesis inhibitor herbicide and with chlorimuron-ethyl, which inhibits the ALS enzyme, show that the chlorophyll content may be used as an intoxication indicator in studies about herbicide selectivity in the culture of castorbean.…”
Section: (B)supporting
confidence: 60%
See 1 more Smart Citation
“…* significant by F test (p≤0.05); ns = non significant. Maciel et al (2011) observed lower chlorophyll content in leaves from the AL Guarany 2002 cultivar, according to the application of isoxaflutole in post-emergence, supporting the intoxication observed between day 7 and 28 DAA. Therefore, results obtained with this carotenoid synthesis inhibitor herbicide and with chlorimuron-ethyl, which inhibits the ALS enzyme, show that the chlorophyll content may be used as an intoxication indicator in studies about herbicide selectivity in the culture of castorbean.…”
Section: (B)supporting
confidence: 60%
“…Another option to control graminaceous species in post-emergence is the use of herbicides that are ACCase inhibitors, such as fluazifopp-butyl, sethoxydim, haloxyfop-methyl, quizalofop-p-ethyl, clethodim, clethodim + fenoxaprop-pethyl, propaquizafop and butroxydim (Maciel et al, 2007(Maciel et al, , 2011(Maciel et al, , 2012Silva et al, 2012;Grichar et al, 2012;Medeiros et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Para o controle de plantas daninhas gramíneas em pós-emergência os herbicidas que apresentaram maior seletividade foram os inibidores da ACCase fluazifop, sethoxydim, haloxifop, clethodim, quizalofop, propaquizafop, fenoxaprop e butroxydim (Maciel et al, 2011). Para o controle de plantas daninhas dicotiledôneas poucos trabalhos são relatados sendo os herbicidas testados pouco seletivos à cultura da mamoneira (Ferreira et al, 2009).…”
Section: Introductionunclassified
“…Examples of herbicide screening work for various crops are available in the literature, such as for castor beans plant (Ricinus communis) and crambe (Maciel et al, 2011;Oliveira Neto et al, 2011a). For C. spectabilis there are few reports of this type of research, and just a few studies on the control of this species carried out in the United States, where it is classified as weed (Wills & McWhorter, 1981;Maddox et al, 2001).…”
Section: Introductionmentioning
confidence: 99%